Association Announcements. (The Accounting Review, 1973)
The article presents an update on issues related to the American Accounting Association (AAA). AAA created a manuscript contest that aims to encourage research among the younger members of the association. Funds will be made available by AAA in the future in order to provide salary support for members who conduct short periods of full-time research activity. Financial assistance grants will be made available by AAA for projects in the areas of educational accounting. A book will be published by AAA after the completion of its project on accounting education.